Pendampingan Masyarakat dalam Praktik Pemeliharaan Sanitasi Lingkungan dan Pengelolaan Air Bersih - Hasanudin, Hasanudin; Saharudin, Saharudin (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Access to clean water and poor sanitation practices remain major health challenges in rural areas. This community service activity aims to enhance the independence of residents of Bale Village in maintaining household environmental sanitation and in the technical management of safe drinking water. The implementation method used a participatory approach, including interactive counseling and live demonstrations of practices within households on 24 April 2026. The activity was attended by 25 participants, consisting of housewives and local community leaders. The results showed a significant increase in participants' skills in performing simple water filtration and disinfection techniques for kitchen water storage containers. 85% of participants correctly demonstrated sanitation hygiene procedures in accordance with environmental health standards. The main benefit of this activity is the growth of critical awareness among the community regarding the risks of water contamination, as well as the technical capacity to mitigate environment-based diseases at the family level. In conclusion, guidance through direct demonstration was highly effective in changing community sanitation behavior compared to conventional lecture methods. Regular monitoring by village health cadres is recommended to ensure the sustainability of these sanitation practices.